Core Values among Newfoundland Fishermen in the 1960s - Whitaker, Ian (Anthropologica, 2022)
In this article the core values of fishermen on the South Coast of Newfoundland in the 1960's are compared with those of a farming/fishing population from the Blasket Islands off western Ireland from a generation earlier in time. The data from which the values are derived consists partly of autobiographical materials, but mainly was obtained through projective narrative tests based on those developed by Kluckhohn and Strodtbeck (1961). The author finds a considerable congruence between the two populations, both in respect of the five values which were the basis of the Kluckhohn study, but also in respect of three others which have emerged in his own work.